An investigation into perceptions of use of visual aids by English teachers at senior high schools in Can Tho : - Lương, Hoàn Hòa (Trường Đại học Cần Thơ, 2021)
In teaching process, as a teacher we need to pay attention on many factors to create an effective lesson plan such as: target, objective, environment... and nowadays Visual Aids (VS) is one of the most popular tool and dealing direct effect on students learning process. Visual Aids can improve students’ long-term memory process. Beside, we do not have deep understand about how to use Visual Aids on right way and in which level Visual Aids(VS) can engage students learning process. In this paper I focus on summarizing teachers’ perceptions on how to use Visual Aids effectively and hypothesis of these teachers’ experience to gain a result on how teachers can use Visual Aids(VS) to engage students learning process.